The legal, political and military scans: from Volume 10. Law, Politics, Militaria, Technology - Saveria Rito (Bibliothecae.it)
Volume 10 of the series La Biblioteca di Francesco Maria II Della Rovere contains the reconstruction bibliographical reconstruction of a portion of the Libraria durantina that belonged to the last Duke of Urbino. The precious collection was semantically organised into seventy shelves and became in 1667 the founding nucleus of the Biblioteca Universitaria Alessandrina in Rome by will of Pope Alexander VII. The Alessandrina also holds the manuscript 50, dating from the first half of the 17th century, which contains the catalogue of the roveresca collection arranged alphabetically by authors and titles. Through transcription of the codex, it was possible to search for the editions in modern catalogues and, subsequently, to identify the specimens belonging to the Duke kept in the Biblioteca Alessandrina, easily recognisable thanks to the possession note ‘VR’ written in ink on the title pages. Enriched with a wealth of photographs, Volume 10 is devoted to seven of the above-mentioned seventy scans and has led to the identification of more than 1,500 editions pertaining to the classes of Ius Canonicum, Ius Civile, Ethica, Oeconomica, Politica, De principatu, De re aulica, Moralia varia, Sententiae, Proverbia, Rhetorica, Poetica, Historica, De re Militari Architectura et Mechanicis. The legal sections have been analysed in the essay that opens the volume, while with this short contribution we would like to focus on some subsections focusing on the education of children and women, praise and criticism of women, and paremiographic literature.